2019
DOI: 10.1093/jopart/muy083
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Minority Discrimination at the Front Line—Combined Survey and Field Experimental Evidence

Abstract: Despite laws of universalistic treatment, bureaucrats have been shown to discriminate against minorities. A crucial question for public administration is how bureaucracies can be organized in ways that minimize illegitimate discrimination. Especially, since theories suggest that prejudices happen unintentionally and particularly under high workload, bureaucrats' working conditions may be important. Four randomized experiments support the notion that bureaucrats discriminate as a way of coping with high workloa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 51 publications
3
68
1
Order By: Relevance
“…This study's approach to examining stereotyping, moreover, has different advantages but also drawbacks when compared to experimental research designs using control and treatment groups. Recent experimental studies have found evidence for direct effects of stereotypes, such as ethnicity, on decision‐making (e.g., Andersen and Guul ). We did not find such direct effects.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study's approach to examining stereotyping, moreover, has different advantages but also drawbacks when compared to experimental research designs using control and treatment groups. Recent experimental studies have found evidence for direct effects of stereotypes, such as ethnicity, on decision‐making (e.g., Andersen and Guul ). We did not find such direct effects.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Within the public administration literature there is a lack of explanatory studies focusing on how cultural beliefs about social groups play a role in the public encounter and affect the judgements of frontline officials (but see Schram et al ; Harrits and Møller ; Andersen and Guul ). This is particularly interesting given the fact that frontline officials are encouraged to be flexible and to be responsive to citizens' situations when making decisions (e.g., Rice ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, physicians show higher levels of implicit racial bias after a highly stressful or dangerously overcrowded shift than before (Johnson et al ). A field experiment shows that school teachers are less prejudiced after a period of reduced workload (Andersen and Guul ). This study argues that public managers might behave in a similar manner and be more prejudiced if they are embedded in poor‐performing organizations and, therefore, under higher work pressure.…”
Section: Employment Discrimination In the Public Sectormentioning
confidence: 99%
“…In a randomised controlled trial,Andersen and Guul (2019) show that discrimination by public school teachers is most acute when workloads are high.3 A willingness-to-pay measure would be problematic in that it captures ability to pay, or household income, rather than only strength of preference. Enrolment gaps due to low-income households having a smaller willingness-to-pay than the subsidised fees are framed as an access barrier rather than a demand-side problem.4 These factors are more fixed than income or employment, which are endogenous with day care enrolment.…”
mentioning
confidence: 99%